2020
DOI: 10.1002/eji.201948278
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GILZ in macrophages limits systemic inflammation while increasing bacterial clearance in sepsis in mice

Abstract: Studies support the beneficial effects of glucocorticoids (GCs) during septic shock, steering research toward the potential role of GC‐induced proteins in controlling excessive inflammatory responses. GILZ is a glucocorticoid‐induced protein involved in the anti‐inflammatory effects of GCs. We investigated whether the overexpression of GILZ specifically limited to monocytes and macrophages (M/M) alone could control inflammation, thus improving the outcome of septic shock in animal models. We also monitored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
(88 reference statements)
2
30
1
Order By: Relevance
“…This combination therapy will be further discussed below. Alternatively, administration of GC-induced proteins, such as GILZ, allows working downstream of the GR and thus provides a potential mechanism to circumvent GCR in sepsis (54,55,103). Injection of a TAT-GILZ fusion construct into mice has been shown to protect against LPS-induced endotoxemia (31).…”
Section: Glucocorticoid Resistance In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…This combination therapy will be further discussed below. Alternatively, administration of GC-induced proteins, such as GILZ, allows working downstream of the GR and thus provides a potential mechanism to circumvent GCR in sepsis (54,55,103). Injection of a TAT-GILZ fusion construct into mice has been shown to protect against LPS-induced endotoxemia (31).…”
Section: Glucocorticoid Resistance In Sepsismentioning
confidence: 99%
“…Administration of low-dose GCs in mice challenged with E. coli decreases the bacterial burden of these mice ( 53 ). Overexpression of the GR-inducible protein GILZ in the whole body ( 54 ) or restricted specifically to macrophages ( 55 ) protects mice against CLP-induced sepsis by limiting systemic inflammation, while bacterial clearance is increased in these mice. It would be interesting to study whether GR Lysmcre mice are also sensitized in bacterial sepsis models such as the CLP model and, if so, whether this could be linked to an increased bacterial burden along with increased inflammation.…”
Section: Role Of Endogenous Gcs In Sepsismentioning
confidence: 99%
“…Further, they showed increased phagocytosis of CD45+ GILZ transgenic cells compared to CD45+ GILZ wild type cells; among other cells, macrophages express CD45. A more recent study showed that a) monocytes and macrophages from septic shock patients and mice have significantly reduced GILZ expression than those of their controls, b) septic transgenic mice, with increased GILZ expression restricted to monocytes and macrophages, displayed lower frequencies of inflammatory monocytes than their littermates and lower plasma levels of inflammatory cytokines, effects which were accompanied with lower blood bacterial counts, c) upregulation of GILZ in monocytes and macrophages increased their phagocytic capacity and d) septic mice with increase GILZ expression in their monocytes and macrophages had increased survival rates (Ellouze et al, 2020). Based on their collective findings, authors propose an essential role for GILZ, and monocytes/macrophages, in pathogenesis of septic shock.…”
Section: Downloaded Frommentioning
confidence: 98%
“…Ellouze et al., in this issue of the European Journal of Immunology [21], showed that GILZ expression in murine macrophages decreases, while TNF and IL‐6 mRNA increases upon LPS treatment. These results were further extended to monocytes isolated from patients with septic shock and confirm earlier findings from others in total blood leukocytes [22].…”
Section: Figurementioning
confidence: 99%
“…The authors also show that when GILZ is overexpressed in transgenic mice under control of the CD68 promotor (expressed in monocytic phagocytes, osteoclasts, circulating and tissue macrophages, including Kupffer cells and microglia), such cells induce much less TNF and more IL‐10 after LPS exposure in vitro as well as in vivo, and the mice are less sensitive in the CLP model of sepsis [21]. Just as GCs can stimulate phagocytosis, GILZ has shown to preserve phagocytosis and thus creating a favorable environment to combat the infection, while protecting the host against excessive systemic inflammation [21]. An interesting question that requires further research is how GILZ activates phagocytosis.…”
Section: Figurementioning
confidence: 99%